Urgensi Pendidikan Moderasi Beragama Sebagai Upaya Menangkal Radikalisme di Kalangan Mahasiswa - Khoirunnissa, Rahma; Syahidin, Syahidin (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2022)
The phenomenon of religious radicalism among the younger generation of Indonesia is alleged to be increasing in the current digital era. In a religious context, religious radicalism can be interpreted as fanatics towards an opinion so as to reject the opinions of others, close the door to dialogue and easily marginalize groups that are different from themselves or their groups, as well as textual religious understanding without seeing and considering the essence of sharia (maqâsid al-sharî'ah). Religious radicalism originated from an exclusive religious perspective, attitude, and behavior. Therefore, the concept of moderate or 'wasathiyyah' should be the basis for policy to counter radical religious narratives. Religious moderation education will be able to become an adhesive between religious spirit and national commitment and become a form of balance in religion to avoid extremism and radicalism among the younger generation, especially students. This study aims to see the application of religious moderation education as a response to the increasing radical mindset of religion among students. The research method used is descriptive qualitative which is a literature study. The results showed that religious moderation education among students can be done through PAI courses, lecturers' approaches and strategies in teaching, guidance on Qur'an Literacy and interpretation, religious mentoring activities carried out by the student activity unit as well as socialization and dialogue about radicalism by student organizations in the campus environment.